Hubungan Pengetahuan Ibu tentang Buku KIA dengan Kunjungan K4 - Apriyanti Sihole (Jurnal Kesehatan, 2020)
The MCH Handbook (Maternal and Child Health) can be used as a basic tool to maximize the quality of life for mothers, children, and families around the world. This book is used as a basic record for mothers and children in more than 30 countries in the world. The MCH book contains records of maternal health from pregnancy to child care up to 6 years of age. The coverage of KIA book ownership at the Teluk Belengkong Health Center was 27% below the district level, namely 59,4%, while the coverage of KI visits was 27% and K4 was 23,03%. This study aims to determine the relationship between a mother's knowledge of the KIA book and K4 visits at the Teluk Belengkong Health Center. This research is quantitative research with a survey method. The number of respondents was 35 people. Knowledge data and the 4th visit were obtained through a checklist sheet and a list of visits to the Puskesmas. The results showed that 65,7% of respondents had good knowledge, while 34,3% of respondents had less knowledge. 40% of respondents had K4 visits and 60% of respondents did not make K4 visits. Statistical test using chi-square with the results of the t value of 19,22 is greater than t table 3,841 at the 95% confidence level. So it can be concluded that there is a relationship between a mother's knowledge of the KIA book and K4 visits at the Teluk Belengkong Community Health Center.